Stosunek rządu Tadeusza Mazowieckiego do problemu tzw. uwłaszczenia nomenklatury i afery alkoholowej - Dudek, Antoni (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article discusses Tadeusz Mazowiecki’s government’s reactions to two pathological phenomena that stirred up intense social emotions. The phenomena were a consequence of the actions taken by the last communist government of the Polish People’s Republic led by Mieczysław Rakowski. First of all, the analysis focuses on actions directed at people from the apparatus of the Polish People’s Republic, who acquired part of the assets of state enterprises and institutions using the new legal regulations. The remainder of the article discusses attempts at counteracting the mass import of alcohol from abroad, which was causing considerable losses to the state budget.